PEMBERDAYAAAN PETERNAKAN KAMBING POTE MELALUI TEKNIK KAWIN SUNTIK UNTUK PENINGKATAN EKONOMI MASYARAKAT BANGKALAN - Sosilowati, Suherni; Hernawati, Tatik; Suprayogi, Tri Wahyu; Candika, Yossy Imam; Supriyadi, Supriyadi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Community Service was conducted to increase local people’s economy by Poté goat population using Artificial Insemination in Alaskokon, Modung, and Bangkalan. The partner in this Community Service are local Poté goat farmers in Alaskokon village, Modung, Bangkalan. The analysis of this situation shows a problem that the Partner has been facing. Even though the Poté population is not lacking, their rearing is conventional where it is not focused on selling but more on saving for when there is no money (Rojokoyo). To tackle this problem, Artificial Insemination was introduced to the Poté. Moreover, socialisation was done by covering various aspects. Sosialisation was given on caring for pregnant does, semen collection using an artificial vagina, and buck semen dilution using different types of extenders such as coconut water, milk, and egg yolk-citrate. Socialisation of the marketing strategy for goats was also given. Artificial Insemination Technology is a solution for improving the goat population. Goats are fast-bred livestock with a relatively short gestation time and can utilise forage like grasses. Artificial Insemination technique can be administered three times in two years to increase the goat population, thus, the local people’s economy may follow. After the programme was completed, farmers were enthusiastic about collecting goat semen and inseminating livestock.